1907 Wash. Sess. Laws 636, ch. 241, § 29, pt. 21. - (:unkn) unknown (My University, 1907)
To regulate or prohibit the loading or storage of gunpowder and combustible or explosive materials in the city, or transporting the same through its streets or over its waters.
Keywords: GUNPOWDER - STORAGE